Interstitial deletion of chromosome 1 (1p21.1p12) in an infant with congenital diaphragmatic hernia, hydrops fetalis, and interrupted aortic arch. Issue 2 (23rd January 2017) - Ibrahim, Masitah; Hunter, Matthew; Gugasyan, Lucy; Chan, Yuen; Malhotra, Atul; Sehgal, Arvind; Tan, Kenneth
Key Clinical Message: We report a case of an infant with congenital diaphragmatic hernia (CDH) and hydrops fetalis who died from hypoxic respiratory failure. Autopsy revealed type B interrupted aortic arch (IAA). Microarray revealed a female karyotype with deletion of chromosome 1p21.1p12. There may be an association between 1p microdeletion, CDH, and IAA. Abstract : We report a case of an infant with congenital diaphragmatic hernia (CDH) and hydrops fetalis who died from hypoxic respiratory failure. Autopsy revealed type B interrupted aortic arch (IAA). Microarray revealed a female karyotype with deletion of chromosome 1p21.1p12. There may be an association between 1p microdeletion, CDH, and IAA.